THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE AT THE ACEH PROVINCIAL LAND OFFICE - Enik Wijayanti; Faisal Matriadi; Marbawi; Sapna Biby; Ikramuddin; Husaini (CV. Radja Publika, 2026)
This study aims to analyse the influence of transformational leadership and job satisfaction on organizational citizenship behaviour with organisational commitment as an intervening variable at the Aceh Provincial Land Office, where the dependent variables of this study are transformational leadership and job satisfaction, the independent variable is organizational citizenship behaviour, and the intervening variable is organisational commitment. The population in this study consists of employees of the Aceh Provincial Land Office, including the North Aceh District office, the Lhokseumawe City office and the Bireuen District office. The sampling technique used was simple random sampling, and a sample of 68 respondents was obtained, all of whom are employees of the Aceh Provincial Land Office. The research method used is quantitative, and data analysis is conducted using path analysis. The results of this study indicate that transformational leadership has a significant effect on organisational commitment, job satisfaction has a significant effect on organisational commitment. Transformational leadership has a significant effect on the organisational citizenship behaviour of employees at the Aceh Provincial Land Office, and job satisfaction has a significant effect on the organisational citizenship behaviour of employees at the Aceh Provincial Land Office. Furthermore, organizational commitment has a significant effect on the organizational citizenship behaviour of employees at the Aceh Provincial Land Office, transformational leadership significantly influences organizational citizenship behaviour through organizational commitment as an intervening variable, and job satisfaction significantly influences organizational citizenship behaviour through organizational commitment as an intervening variable.